Influence Of Casting Temperature On The Structural Behavior Of Concrete - Panhyar, M. A.; Shah, S. N. R.; Shaikh, F. A.; Jhatial, A. A. (Engineering, Technology & Applied Science Research, 2019)
Concrete is the most preferred construction and building material and its demand is not expected to diminish in the near future. The properties of concrete are affected by various factors, one of them is the temperature at casting. This experimental work was carried out in order to study the effect of high temperature on workability, and compressive and flexural tensile strength of concrete. It was found that higher temperatures caused water content evaporation from the mix during casting, causing reduction in workability, but simultaneously increased the strength compared to concrete cast at controlled temperatures).